Ω versus graviphoton - Ahmad Zein Assi (Nuclear Physics B, 2019)
In this work, I study the deformation of the topological string by Ω¯, the complex conjugate of the Ω-deformation. Namely, I identify Ω¯ in terms of a physical state in the string spectrum and verify that the deformed Yang-Mills and ADHM actions are reproduced. This completes the study initiated in [1] where we show that Ω¯ decouples from the one-loop topological amplitudes in heterotic string theory. Similarly to the N=2⋆ deformation, I show that the quadratic terms in the effective action play a crucial role in obtaining the correct realisation of the full Ω-deformation. Finally, I comment on the differences between the graviphoton and the Ω-deformation in general and discuss possible Ω¯ remnants at the boundary of the string moduli space.